The Contribution of Neutrophil Extracellular Traps to Coagulopathy in Patients with COVID-19-Related Thrombosis - Carolyn Enochs; Gabriela Delevati Colpo; Lucy Couture; Lynae Baskin; Ana E. Cahuiche; Eunyoung Angela Lee; Shahid Nimjee; Louise D. McCullough (Viruses)
COVID-19 is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and is associated with hypercoagulability and increased incidence of thrombotic events. In this study, we investigated the levels of neutrophil extracellular trap biomarkers and von Willebrand factor to assess if these could predict the occurrence of a thrombotic event in COVID-19 patients. We enrolled 202 patients hospitalized with symptomatic COVID-19 infection. Of those, 104 patients did not experience any type of thrombotic events before or during their hospitalization. These patients were compared to the other cohort of 98, who experienced thrombotic events before or during their hospitalization. In total, 61 patients who experienced thrombotic events had the event after initial blood collection, so the predictive capacity of biomarkers in these patients was evaluated. Citrullinated histone H3 was the best predictive biomarker for thrombotic events in COVID-19 regardless of age, sex, and race; disease severity was also a significant predictor in most thrombotic event groups. These results may better inform treatment and prophylaxis of thrombotic events in COVID-19 and similar viral illnesses in the future to improve outcomes and reduce mortality.